Odpowiedzi

2010-04-05T18:03:58+02:00
P=d/mRT /*mRT
pmRT=d /:PRT
m=d/PRT

f=9/5c+32 /*5c+32
5fc+32f=9 /:f
5c+32=9/f /-32
5c=9/f -32 /5
c= 9/f-32//5 (od 9/f trzeba odjac 32 i podzielic przez 5-trudno to zapisac)

s=vt+at2/2 /*2
2s=2vt+at /-2vt
2s-2vt=at /:t
a=2s-2vt/t

d) F=G Mm/r2 /*r2
Fr2=GMm /:GM
m=Fr2/GM

6 3 6
2010-04-05T18:12:46+02:00
A) P=d/mRT; M
P=d/mRT/*Mrt
PMrt=d/:Prt
M=d/Prt
b) f=9/5c+32; c
f=9/5c+32
-9,5c=32-f/:(-9,5)
c=32-f/-9,5
c) s=vt+at2/2; a
s=vt+at2/2; a
-at2/2=vt-s/:(-t2/2)
a=vt-s/-t2/2
d) F=G Mm/r2; m
F=G Mm/r2/:Gr2
F/Gr2=Mm/:M
F/Gr2/m

zad2
a) t+x/a-5x
b) p=a+x+ax
p-a=x+ax/;a
p-a/a=x+X/a/*a
p-a=x2/pierwiastek
pierwiastek p-a=x
x=pierwiastek p-a

c) m= (x+1)p-3x
m=xp+p-3x
m-p=xp-3x/:p-3
m-p/3-x=x
x=m-p/3-x
d) w= 1/x+p
w-p=1/x/*1
w-p=x
x=w-p

1 zad chyba dobrze co do 2 nie jestem pewna
5 4 5
2010-04-05T18:14:43+02:00
Zad 1
a
P=d/mRT
PmRT = d
m = d/PRT
b
f=9/5c+32
f(5c + 32) = 9
f5c + f32 = 9
f5c = 9 - f32
c = (9 - f32)/f5
c
s=vt+at2/2
2s = vt + at²
at² = 2s - vt
a = (2s - vt)/t²
d
F=G Mm/r2
Fr2 = GMm
m = Fr2/GM
zad 2
a) t+x/a-5x
at + x - 5ax
at = 5ax - x
at = x(5a - 1)
x = at/(5a - 1)
b) p=a+x+ax
p - a = x(1 + a)
x = (p - a)/(1 + a)
c) m= (x+1)p-3x
m = px + p - 3x
m - p = x(p - 3)
x = (m- p)/(p - 3)
d) w= 1/x+p
xw = 1 + xp
xw - xp = 1
x(w - p) = 1
x = 1/(w - p)
4 5 4